Customer perception towards service quality provided by Tabung Haji Kuala Lumpur / Ameerul Akhyar Muhthar - Muhthar, Ameerul Akhyar (2016)
Tabung Haji (TH) birth from the idea or working paper presented by the Royal Professor Ungku Aziz titled, “Plan to improve the Economy Perspective Pilgrims" in 1959. The functions of this organization are to enable Muslims to save gradually to support their expenditure during pilgrimage and for beneficial purposes, to enable Muslims to have active and effective participations in investment activities permissible in Islam through their savings and to protect, safeguard interests and ensures welfare of pilgrims during pilgrimage by providing various facilities and services. The purpose of this research is to study the customer perception towards the service quality provided by Tabung Haji Kuala Lumpur. The research used the service quality (SERVQUAL) dimensions. There are 5 dimensions in SERVQUAL which are reliability, responsiveness, assurance, empathy and tangible. This dimension will be used to identify customer perception towards service quality provided by Tabung Haji Kuala Lumpur as quality services depend on the Tabung Haji Kuala Lumpur employee's performance and their ability to provide the services.